14.1k views
2 votes
Apply the distributive property to create an equivalent expression.

(m−3+4n)⋅(−8)=(m-3+4n)\cdot (-8) =(m−3+4n)⋅(−8)=left parenthesis, m, minus, 3, plus, 4, n, right parenthesis, dot, left parenthesis, minus, 8, right parenthesis, equals
ANSWER ASAP

Apply the distributive property to create an equivalent expression. (m−3+4n)⋅(−8)=(m-example-1
User Woworks
by
5.4k points

2 Answers

4 votes

Answer:−8m+24−32n

.................

Apply the distributive property to create an equivalent expression. (m−3+4n)⋅(−8)=(m-example-1
User ZVictor
by
5.2k points
6 votes

Answer:

it is -1

Explanation:

m= - (4 = m ) + 2

m= -4−m+2

m = −2 −m

m + m = -2 - m + m

2m = -2

2m/2 = -2/2

m= - 1

Apply the distributive property to create an equivalent expression. (m−3+4n)⋅(−8)=(m-example-1
User Hevele
by
5.5k points